José Alcina Franch y los códices mesoamericanos - León-portilla, Miguel (Revista Española de Antropología Americana, 2003)
This paper analyzes the contributions of José Alcina Franch to study of Mesoamerican Codex. It reviews his early work, «Fuentes indígenas de Méjico», his editions of Códice Veitia and Códice del Museo del Ejército de Madrid, Calendarios zapotecos and his Códices mexicanos.